Extracellular peptidase hunting for improvement of protein production in plant cells and roots - Lallemand, Jérôme; Bouché, Frédéric; Desiron, Carole; Stautemas, Jennifer; de Lemos Esteves, Frédéric; Périlleux, Claire; Tocquin, Pierre (Frontiers in Plant Science, 2015)
Plant-based recombinant protein production systems have gained an extensive interest over the past few years, because of their reduced cost and relative safety. Although the first products are now reaching the market, progress are still needed to improve plant hosts and strategies for biopharming. Targeting recombinant proteins toward the extracellular space offers several advantages in terms of protein folding and purification, but degradation events are observed, due to endogenous peptidases. This paper focuses on the analysis of extracellular proteolytic activities in two production systems: cell cultures and root-secretion (rhizosecretion), in Arabidopsis thaliana and Nicotiana tabacum. Proteolytic activities of extracellular proteomes (secretomes) were evaluated in vitro against two substrate proteins: bovine serum albumin (BSA) and human serum immunoglobulins G (hIgGs). Both targets were found to be degraded by the secretomes, BSA being more prone to proteolysis than hIgGs. The analysis of the proteolysis pH-dependence showed that target degradation was mainly dependent upon the production system: rhizosecretomes contained more peptidase activity than extracellular medium of cell suspensions, whereas variations due to plant species were smaller. Using class-specific peptidase inhibitors, serine and metallopeptidases were found to be responsible for degradation of both substrates. An in-depth in silico analysis of genomic and transcriptomic data from Arabidopsis was then performed and led to the identification of a limited number of serine and metallo-peptidases that are consistently expressed in both production systems. These peptidases should be prime candidates for further improvement of plant hosts by targeted silencing.